Characteristics of Plasmodium knowlesi Malaria based on the results of PCR examinations in Aceh Besar District. Issue 1 (March 2021) - Puetri, N R; Fahrimal, Y; Farida; Salmiaty
Abstract: Malaria is a disease that conducted the health problems in Indonesia. Human malaria is caused by Plasmodium. There are 5 types of plasmodium, which were known to be able to infect humans, namely Plasmodium vivax, Plasmodium falciparum, Plasmodium malariae, Plasmodium ovale, and Plasmodium knowlesi. The increasing of malaria cases due to Plasmodium knowlesi in Aceh Besar District for the period 2019-2020 be the fundamental of this research related to the proportion of patient characteristics, which include: sex, age, occupation, domicile and health facilities that carry out examinations and provide treatment and the connection with the PCR examination results. This research applied a descriptive method with cross-sectional design. The total sample were 39 samples with a total positive PCR sample were 16 samples that consists of 81.3% of male gender (13 people), 62.5% of adult (10 people), 56.3% of worker (9 people), 75% of native (12 people) and 81.3% of the people from Lembah Seulawah health center (13 people). The characteristics patients infected by Plasmodium knowlesi malaria in the Aceh Besar District are: Male, adult, working, native population and the highest number were in the Lembah Seulawah Health Center.